Knowledge details in web forums: how high or low above the ground? - Abd. Rozan, Mohd. Zaidi; Mikami, Yoshiki (2006)
While entertainment web forums provide dynamic medium for interaction, not many researchers feel the need to go deeply into the contents. One of the reasons behind this attitude lays on a widely perceived assumption that web forums does not deal with knowledge matter and has the inclination to take place only as a small talk. In this paper, we will mainly inspect the components of knowledge as are being handled by the six service-men of Kipling’s 5W1H framework. Based on our observation on a learning zone that contains 35 forum topics and 789 messages in a web forum (http://asamboi.org), we found out at least several topics are dealing with deep knowledge contents. From our analysis, we have found that the depth of knowledge details is reasonably significant particularly when responding to specific question demand. On average the depth of details obtained were ranked as ‘Who’ Siapa, ‘What’ Apa, ‘How’ Bagaimana, ‘Why’ Kenapa, ‘Where’ Mana and ‘When’ Bila once sorted descendingly. We conclude that web forums are a good web-resource for digital age learning styles as it provides detailed knowledge for networked learning.